Czynniki wspierające powstawanie i rozwój świadomości emerytalnej jako instrumentu pobudzania indywidualnej zapobiegliwości o przyszłość emerytalną - Klimkiewicz, Aldona (Annales. Etyka w Życiu Gospodarczym, 2012)
Projections for replacement rate achievable from two mandatory pillars of the pension system indicate a significant reduction in retirement income compared to regular professional activity. The designers of the new philosophy of retirement have made an assumption that all three pillars will play equivalent role in providing retirement income. They have also assumed that the participants of the pension system will be kept informed about the height of the expected benefits derived from the first pillar and the amount of funds raised in the second pillar. Forecast of low (unsatisfactory) benefits from a compulsory part of the system is supposed to persuade people to make informed decisions aimed at increasing retirement income.